Low bit rate speech coding standards - Shah, Asadullah; Shaikh, Asadullah (IIUM Press, 2011)
The main area of speech coding standards is digital telephone, cellular mobile digital radio, and satellite fixed, and mobile system. Various digital speech coding standards which are currently in use and others are being developed for such applications. Most of these standards are International Telecommunication Union (lTU) based recommendations, Inmarsat-M, Japanese or American standards. In this chapter all such standards are provided along with their year of standardization, coding type, bit rate and Mean Opinion Scores (MOS) which is a subjective, perceptual judgment